VOLATILIZATION KINETICS OF SILICON CARBIDE IN REDUCING GASES: AN EXPERIMENTAL STUDY WITH APPLICATIONS TO THE SURVIVAL OF PRESOLAR GRAINS IN THE SOLAR NEBULA - Mendybaev R.A.; Beckett J.R.; Grossman L.; Stolper E.; Cooper R.F.; Bradley J.P. (My University, 2002)
The volatilization kinetics of single crystal α-SiC, polycrystalline β-SiC, and SiO2 (cristobalite or glass) were determined in H2-CO2, CO-CO2, and H2-CO-CO2 gas mixtures at oxygen fugacities between 1 log unit above and 10 log units below the iron-wustite (IW) buffer and temperatures in the range 1151 to 1501°C. Detailed sets of experiments on SiC were conducted at 2.8 and 6.0 log units below IW (IW-2.8 and IW-6.0) at a variety of temperatures, and at 1300°C at a variety of oxygen fugacities. Transmission electron microscopic and Rutherford backscattering spectroscopic characterization of run products shows that the surface of SiC exposed to IW-2.8 is characterized by a thin (<1  thick), continuous layer of cristobalite. sic exposed to iw-6.0 lacks such a (or its thickness is <0.01 ), although some sio2 was found within pits and along incised grain boundaries.In H2-CO2 gas mixtures above ~IW-3, the similarity of the SiC volatilization rate and of its dependence on temperature and fO2 to that for SiO2 suggests that SiC volatilization is controlled by volatilization of a SiO2 layer that forms on the surface of the SiC. With decreasing log fO2 from ~IW-3 to ~IW-6, the SiC volatilization rate is constant at constant temperature, whereas that for SiO2 increases. The independence of the SiC volatilization rate from the gas composition under these conditions suggests that the rate-controlling step is a solid-solid reaction at the internal SiC/SiO2 interface. For gas compositions more reducing than ~IW-6, the SiC volatilization rate increases with decreasing fO2, with both bare SiC surfaces and perhaps silica residing in pits and along incised grain boundaries contributing to the overall reaction rate.If the volatilization mechanism and reaction rate in the solar nebula were the same as in our H2-CO2 experiments at IW-6.0, then estimated lifetimes of 1-μm-diameter presolar SiC grains range from several thousand years at ~900°C, to ~1 yr at 1100°C, ~1 d at 1300°C, and ~1 h at 1400°C. The corresponding lifetimes for 10-μm SiC grains would be an order of magnitude longer. If the supply of oxidants to surfaces of presolar SiC grains were rate limiting-for example, at T > 1100°C for Pt°t= 10-6 atm and sticking coefficient = 0.01, then the calculated lifetimes would be about 10 yr for 10-μm-diameter grains, essentially independent of temperature. The results thus imply that presolar SiC grains would survive short heating events associated with formation of chondrules (minutes) and calcium-, aluminum-rich inclusions (days), but would have been destroyed by exposure to hot (=<900°C) nebular gases in less than several thousand years unless they were coated with minerals inert to reaction with a nebular gas.